GAMYB-like Genes, Flowering, and Gibberellin Signaling in Arabidopsis - Gocal, Gregory F.W. (American Society of Plant Physiologists, 2001)
We have identified three Arabidopsis genes with GAMYB-like activity, AtMYB33, AtMYB65, and AtMYB101, which can substitute for barley (Hordeum vulgare) GAMYB in transactivating the barley α-amylase promoter. We have investigated the relationships between gibberellins (GAs), these GAMYB-like genes, and petiole elongation and flowering of Arabidopsis. Within 1 to 2 d of transferring plants from short- to long-day photoperiods, growth rate and erectness of petioles increased, and there were morphological changes at the shoot apex associated with the transition to flowering. These responses were accompanied by accumulation of GAs in the petioles (GA(1) by 11-fold and GA(4) by 3-fold), and an increase in expression of AtMYB33 at the shoot apex. Inhibition of GA biosynthesis using paclobutrazol blocked the petiole elongation induced by long days. Causality was suggested by the finding that, with GA treatment, plants flowered in short days, AtMYB33 expression increased at the shoot apex, and the petioles elongated and grew erect. That AtMYB33 may mediate a GA signaling role in flowering was supported by its ability to bind to a specific 8-bp sequence in the promoter of the floral meristem-identity gene, LEAFY, this same sequence being important in the GA response of the LEAFY promoter. One or more of these AtMYB genes may also play a role in the root tip during germination and, later, in stem tissue. These findings extend our earlier studies of GA signaling in the Gramineae to include a dicot species, Arabidopsis, and indicate that GAMYB-like genes may mediate GA signaling in growth and flowering responses.